Molding material

By using cellulose fibers, adhesives and polyurethane fibers in molding materials, optimizing the molecular weight distribution of resin and adding crosslinking agents, the problems of fiber shedding and dust generated during the melting process of molding materials are solved, and high strength and shape stability are achieved shaped body.

CN119220015APending Publication Date: 2024-12-31SEIKO EPSON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410860994.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing molding materials containing cellulose fibers and resins are prone to cause fibers to fall off during the melt forming process, resulting in dust, and it is difficult to maintain strength and shape stability at high temperatures.

Method used

Using molding materials containing cellulose fibers, adhesives and polyurethane fibers, the molecular weight distribution curve of the resin has a maximum value in the range of 50,000 to 150,000 and 75,000 to 300,000, and the area value of the maximum value 2 is less than the maximum value 1, combined with The crosslinking agent and an appropriate amount of flame retardant optimize the resin molecular weight distribution through the GPC method to enhance the high molecular weight components of the resin.

Benefits of technology

It effectively inhibits fiber shedding and dust generation, improves the impact strength, bending strength and heat resistance of the molded body, and ensures the shape stability and strength of the molded body at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004919178000000011
    Figure HDA0004919178000000011
  • Figure HDA0004919178000000021
    Figure HDA0004919178000000021
  • Figure HDA0004919178000000031
    Figure HDA0004919178000000031
Patent Text Reader

Abstract

The present invention provides a molding material capable of better suppressing the generation of dust even when there is a molding thermal history. A molding material according to one embodiment of the present invention is a molding material containing cellulose fibers and a resin containing a binder and polyurethane fibers, the resin having a maximum value of 1,000,000-1,000,000 at a weight-average molecular weight in a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and having an average molecular weight of 1,000,000-1,000,000 at a maximum value of 1,000,000-1,000,000 at a weight-average molecular weight of 1,000,000-1,000,000 at a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent. When the weight-average molecular weight is 75000-300000, the polymer has a maximum value 2, and the area value of the maximum value 2 is smaller than the area value of the maximum value 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molding material. Background Art

[0002] In the past, molded bodies made of materials containing cellulose fibers and resins are known. For example, in Patent Document 1, a cellulose fiber-reinforced thermoplastic resin molded body containing a thermoplastic resin, cellulose fibers, and organic fibers different from the cellulose fibers is proposed for the purpose of providing a molded body having both a sufficiently high bending elastic modulus (rigidity) and excellent impact strength.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 7097521 Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] However, in conventional materials, when there is a molding heat history such as a case where a molded product or a gate material during molding is melted and pelletized and then molded again, fibers may fall off and generate dust.

[0008] Technical solutions for solving technical problems

[0009] One embodiment of the molding material according to the present invention is:

[0010] A molding material containing cellulose fibers and resin,

[0011] The resin contains a binder and polyurethane fibers,

[0012] The resin has a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and has a local maximum value 1 when the weight average molecular weight is 50,000 to 150,000, and has a local maximum value 2 when the weight average molecular weight is 75,000 to 300,000.

[0013] The area value of the maximum value 2 is smaller than the area value of the maximum value 1. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a figure (Table 1) which shows the composition of the raw materials of the molding material of each Example and each Comparative Example, the molding method, and the evaluation results of the molded product.

[0015] Figure 2 It is a figure (Table 2) which shows the composition of the raw materials of the molding material, the molding method, and the evaluation results of the molded product in each Example and each Comparative Example.

[0016] Figure 3 It is a graph (Table 3) showing the composition of the raw materials of the molding materials of each Example and each Comparative Example, the molding method, and the evaluation results of the molded products. DETAILED DESCRIPTION

[0017] The following are embodiments of the present invention. The embodiments described below illustrate examples of the present invention. The present invention is not limited to the following embodiments, but also includes various modifications implemented within the scope of the present invention. It should be noted that all the structures described below are not necessarily required structures of the present invention.

[0018] 1. Molding materials

[0019] The molding material involved in one embodiment of the present invention is a molding material containing cellulose fibers and a resin, the resin containing a binder and polyurethane fibers, and the resin has a maximum value 1 when the weight average molecular weight is 50,000 to 150,000, and has a maximum value 2 when the weight average molecular weight is 75,000 to 300,000 in a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and the area value of the maximum value 2 is smaller than the area value of the maximum value 1.

[0020] In a cellulose fiber-reinforced thermoplastic resin molded body containing a thermoplastic resin, cellulose fibers, and organic fibers different from the cellulose fibers, fibers significantly fall off the molded body, and there is a problem that the molded body is not suitable for use in an environment where dust generation and the like are a problem, such as parts having a flow path for a fluid or parts arranged around the parts, ink cartridges, various containers, various daily utensils, etc.

[0021] Recently, it has been found that a molding material containing cellulose fibers, a binder, and polyurethane fibers can be suitably used for production of a molded body containing cellulose fibers, having excellent impact strength and bending strength, and suppressing dust generation.

[0022] The reasons why it can be considered that such an effect can be obtained are as follows. That is, by containing cellulose and adhesive with theoretically high strength and excellent shape retention, and containing polyurethane with excellent compatibility and affinity with cellulose fiber and adhesive, the functions of these components can be prevented and suppressed from canceling each other, so that the functions of these components can be fully exerted. More specifically, when the molding of the molding material is used, or in the molding made of the molding material, the functions of cellulose fiber and adhesive can be fully exerted, and the wettability of the adhesive relative to cellulose fiber can be improved simultaneously, and the interface peeling between the different components constituting the molding can be appropriately prevented and suppressed. As a result, it can be considered that the above-mentioned effect can be obtained. In addition, since the interface peeling between the different components constituting the molding can be appropriately prevented and suppressed, the molding that effectively prevents the generation of dust and other problems can be obtained.

[0023] In addition, by containing cellulose fibers, which are abundant natural raw materials derived from plants, environmental issues and the conservation of buried resources can be well addressed, and it is also advantageous from the viewpoints of stable supply of molding materials or molded bodies made using the same, cost reduction, etc. In addition, cellulose fibers are components that are also contained in large quantities in waste paper, old cloth, etc., in addition to raw pulp, and are also advantageous from the viewpoint of promoting effective recycling of resources.

[0024] In addition, although waste clothing and the like contain a large amount of polyurethane fibers, when mixed with other components such as in blended products, it is difficult to separate them from the other components. In addition, since toxic gases are generated during heat processing at above 200°C, it has been difficult to reuse and incinerate them in the past. However, through the present invention, the polyurethane fibers contained in waste clothing and the like can be appropriately reused.

[0025] In contrast, when the above conditions are not met, satisfactory results cannot be obtained. For example, even if cellulose fibers and adhesives are contained, if polyurethane is not contained, the wettability of the adhesive relative to the cellulose fibers cannot be sufficiently excellent, and in the molded body manufactured using the molding material, interface peeling between different components is likely to occur, and the strength of the molded body cannot be sufficiently excellent. In addition, the molded body manufactured using the molding material is prone to the problem of dust generation.

[0026] Even if cellulose fibers and polyurethane fibers are contained, if no binder is contained, the moldability of the molded article is significantly reduced, making it difficult to produce the molded article itself.

[0027] Even if the binder and the polyurethane fibers are contained, if the cellulose fibers are not contained, the above-mentioned effect of containing the cellulose fibers cannot be exerted, and the strength of the molded body produced using the molding material is significantly reduced.

[0028] On the other hand, if there is a molding heat history in which the molded product or the gate material during molding is melted and pelletized and then molded again, the resin in the molding material decomposes due to heat, causing various properties to deteriorate. In particular, low-temperature melting resins that melt at less than 200°C are prone to thermal decomposition. In addition, if there is a molding heat history, the fiber falls off from the molded body more significantly, making it difficult to suppress the generation of dust.

[0029] Therefore, the present inventors have conducted intensive studies and have found that dust generation can be excellently suppressed even in the case of a molding heat history by making the resin containing the binder and the polyurethane fiber contain a moderate amount of high molecular weight components.

[0030] Hereinafter, various raw materials contained in the molding material will be described.

[0031] 1.1 Cellulose fiber

[0032] The molding material according to the present embodiment contains cellulose fibers.

[0033] The cellulose fibers are components that greatly contribute to the retention of the shape of a molded body produced using the molding material according to the present embodiment and that greatly affect the properties of the molded body, such as strength.

[0034] Cellulose is an abundant natural material derived from plants. Therefore, by using cellulose fibers, environmental problems or the saving of buried resources can be well addressed, and it is also preferred from the viewpoints of stable supply of molding materials or molded bodies made using the same, cost reduction, etc. In addition, cellulose fibers have a particularly high theoretical strength among various fibers, which is also advantageous from the viewpoint of improving the strength of molded bodies.

[0035] Examples of the cellulose fiber include cotton, linen, rayon, and cuprammonium fibers. As the cellulose fiber, virgin pulp may be used, or waste paper, old cloth, and the like may be recycled.

[0036] Cellulose fibers are usually mainly composed of cellulose, but may contain components other than cellulose. Examples of such components include hemicellulose and lignin.

[0037] Furthermore, as the cellulose fibers, cellulose fibers subjected to treatment such as bleaching may be used.

[0038] The average length of the cellulose fibers is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and further preferably 100 μm or more and less than 400 μm.

[0039] As a result, there is a tendency that the shape stability, strength, etc. of the molded body manufactured using the molding material can be made more excellent. In addition, there is a tendency that dust generation in the molded body manufactured using the molding material can be more effectively prevented and suppressed. In particular, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed. In addition, sometimes it is possible to more effectively prevent the generation of unintentional unevenness on the surface of the molded body manufactured using the molding material. It should be noted that the fiber length can be obtained by a method based on ISO 16065-2:2007.

[0040] The average diameter of the cellulose fibers is not particularly limited, but is preferably less than 100 μm, more preferably 3 μm or more and less than 50 μm, and further preferably 5 μm or more and less than 20 μm.

[0041] As a result, there is a tendency that the shape stability, strength, etc. of the molded body manufactured using the molding material can be made more excellent. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed. In addition, there is a tendency that unintentional unevenness can be more effectively prevented from occurring on the surface of the molded body manufactured using the molding material.

[0042] The average aspect ratio of the cellulose fibers, that is, the average length relative to the average diameter, is not particularly limited, but is preferably 10 or more and 1000 or less, and more preferably 15 or more and 100 or less.

[0043] As a result, there is a tendency that the shape stability, strength, etc. of the molded body manufactured using the molding material can be made more excellent. In addition, there is a tendency that dust generation in the molded body manufactured using the molding material can be more effectively prevented and suppressed. In particular, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed. In addition, sometimes it is possible to more effectively prevent the generation of unintentional unevenness on the surface of the molded body manufactured using the molding material.

[0044] The content of the cellulose fiber is preferably 2% by mass or more and 40% by mass or less relative to the total mass of the molding material, more preferably 2% by mass or more and 35% by mass or less, further preferably 2% by mass or more and 30% by mass or less, particularly preferably 2% by mass or more and 25% by mass or less, particularly preferably 2% by mass or more and 20% by mass or less. If the content of the cellulose fiber is within the above range, there is a tendency that the stability of the shape, strength, etc. of the molding manufactured using the molding material can be made more excellent. In addition, even in the case of a molding thermal history, there is a tendency that dust generation can be better suppressed.

[0045] 1.2 Resin

[0046] The molding material according to the present embodiment contains a resin, and the resin contains a binder and polyurethane fibers.

[0047] The content of the resin is preferably 50% by mass or more and 99% by mass or less, more preferably 60% by mass or more and 95% by mass or less, and further preferably 70% by mass or more and 95% by mass or less relative to the total mass of the molding material. Thus, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0048] 1.2.1 Adhesive

[0049] By making the resin in the molding material according to the present embodiment contain a binder, the toughness of a molded body produced using the molding material according to the present embodiment can be improved, and the impact resistance of the molded body can be made sufficiently excellent.

[0050] The binder may be any binder as long as it can exhibit the above-mentioned function, and is generally a resin material.

[0051] The resin material used as the adhesive, i.e., the adhesive resin, includes, for example, polyolefins such as polyethylene and polypropylene, polyesters such as aliphatic polyesters and aromatic polyesters, and it is preferred to use one selected therefrom or to use two or more in combination, and more preferably at least one of polyolefins and aliphatic polyesters.

[0052] This can improve the affinity between the adhesive and the polyurethane, and even when there is a molding heat history, there is a tendency that the generation of dust can be better suppressed.

[0053] Aliphatic polyester is a polyester having a chemical structure that does not have aromaticity, and is a polyester having a chemical structure in which all the constituent monomers do not have aromaticity. Examples of aliphatic polyesters include aliphatic polyesters in which the polycarboxylic acid component and the polyol component as constituent monomers both have aliphatic alkylene groups. In addition, aliphatic polyesters may also be composed of monomers having hydroxyl groups and carboxyl groups in the molecule. Examples of aliphatic polyesters composed of monomers having hydroxyl groups and carboxyl groups in the molecule include polylactic acid and the like.

[0054] In the case where the aliphatic polyester has a chemical structure formed by polymerizing a polycarboxylic acid component having an aliphatic alkylene group and a polyol component having an aliphatic alkylene group, the aliphatic polyester preferably has a chemical structure formed by condensing an alkylene dicarboxylic acid having an alkylene group with a carbon chain length of 2 or more and 6 or less and an alkylene glycol having an alkylene group with a carbon chain length of 2 or more and 8 or less. As a result, there is a tendency that the adhesive can function more effectively, the compatibility with polyurethane can be improved, and the impact strength and bending strength of the molded body manufactured using the molding material can be improved. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0055] The carbon chain length of the alkylene group of the alkylene dicarboxylic acid is preferably 2 or more and 6 or less, more preferably 2 or more and 5 or less, and even more preferably 2 or more and 4 or less. As a result, the impact strength and bending strength of the molded body produced using the molding material tend to be more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0056] The alkylene group of the alkylene dicarboxylic acid may have a branched structure, but is preferably a straight-chain alkylene group. This tends to make the impact strength and bending strength of a molded body produced using the molding material more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0057] Examples of the alkylene dicarboxylic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid, and it is preferred to use one or a combination of two or more selected from these.

[0058] The carbon chain length of the alkylene group of the alkylene glycol is preferably 2 or more and 8 or less, more preferably 2 or more and 6 or less, and even more preferably 3 or more and 5 or less. As a result, the impact strength and bending strength of the molded body produced using the molding material tend to be more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0059] The alkylene group of the alkylene glycol may have a branched structure, but is preferably a straight chain structure. As a result, there is a tendency that the impact strength and bending strength of the molded body produced using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0060] Examples of the alkylene glycol include 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol. It is preferred to use one selected from these or two or more selected from these.

[0061] Specific examples of aliphatic polyesters containing alkylene dicarboxylic acids and alkylene glycols satisfying the above conditions as monomer components include polybutylene succinate, polybutylene succinate-adipate, polyethylene adipate, etc. It is preferred to use one selected from them or to use two or more in combination, among which polybutylene succinate, polybutylene succinate-adipate, and polyethylene adipate are more preferred.

[0062] These are biodegradable materials that can more appropriately reduce the environmental load caused by the molded product. In addition, these materials are easily and stably available at a relatively low price. Therefore, it is also advantageous from the viewpoints of stable supply of molding materials or molded bodies, cost reduction, etc.

[0063] The content of the binder is preferably 35% by mass or more and 94% by mass or less relative to the total mass of the molding material, more preferably 40% by mass or more and 92% by mass or less, and further preferably 50% by mass or more and 90% by mass or less. Thus, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made more excellent. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0064] When the content of cellulose fibers in the molding material involved in the present embodiment is set to XC [mass %] and the content of the binder is set to XB [mass %], it is preferred to satisfy the relationship of 0.01≤XC / XB≤0.60, more preferably satisfy the relationship of 0.02≤XC / XB≤0.50, and further preferably satisfy the relationship of 0.03≤XC / XB≤0.45. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0065] 1.2.2 Polyurethane fiber

[0066] The resin in the molding material involved in the present embodiment contains polyurethane fiber. Polyurethane fiber is a kind of resin fiber, which is a fiber composed of a material containing polyurethane. It should be noted that the form of the polyurethane fiber in the molding material involved in the present embodiment can be fibrous, or can be an irregular shape after a part or all of the fiber is melted and solidified. Therefore, the polyurethane fiber in the molding material can be fibrous, irregularly shaped or a mixture thereof. The same is true for other resin fibers other than polyurethane fibers.

[0067] The polyurethane fibers are generally melted during the production process of a molded body using the molding material according to the present embodiment, particularly during the heating process during molding.

[0068] Polyurethane is a component having excellent affinity with both the aforementioned cellulose fibers and the binder.

[0069] Such polyurethane functions as a compatibilizer when using the molding material involved in the present embodiment to manufacture a molded body, thereby improving the compatibility of cellulose fibers and adhesives. Thus, the wettability of the adhesive relative to the cellulose fibers is improved, and the bending strength of the molded body manufactured using the molding material involved in the present embodiment can be improved. In addition, by containing an adhesive, the heat resistance of the molded body manufactured using the molding material involved in the present embodiment can also be improved.

[0070] The polyurethane constituting the polyurethane fiber may be any compound in which an amino group and an alcohol group react via a carbonyl group to form a new covalent bond between the nitrogen of the amine and the carbon of the carbonyl group, and polyurethane is preferred.

[0071] When the polyurethane fiber is a fiber composed of a material containing polyurethane, the number average molecular weight of the polyurethane is preferably 20,000 to 300,000, more preferably 30,000 to 200,000, and further preferably 40,000 to 150,000.

[0072] Thus, the affinity and compatibility of polyurethane with respect to cellulose fiber or adhesive can be made more excellent, and there is a tendency that the impact strength and bending strength of the molded body made using the molding material can be made more excellent. In addition, even in the case of a molding thermal history, there is also a tendency that dust generation can be better suppressed.

[0073] The polyurethane fiber is in a fiber form in the molding material according to the present embodiment, but a part of the polyurethane fiber may be in a powder form or a molten state, for example.

[0074] The average length of the polyurethane fibers is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and further preferably 100 μm or more and less than 400 μm. This tends to improve the impact strength and bending strength of a molded body made using the molding material. In addition, even in the case of a molding heat history, dust generation tends to be better suppressed.

[0075] The average diameter of the polyurethane fiber is not particularly limited, but is preferably less than 100 μm, more preferably 3 μm or more and less than 50 μm, and further preferably 5 μm or more and less than 20 μm. This tends to make the impact strength and bending strength of the molded body made using the molding material more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0076] The average aspect ratio of the polyurethane fiber, i.e., the average length relative to the average diameter, is not particularly limited, and is preferably 10 or more and 1000 or less, and more preferably 15 or more and 100 or less. Thus, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made more excellent. In addition, even in the case of a molding thermal history, there is a tendency that dust generation can be better suppressed.

[0077] The content of the polyurethane fiber is preferably 2% by mass or more and 40% by mass or less relative to the total mass of the molding material, more preferably 3% by mass or more and 35% by mass or less, further preferably 3% by mass or more and 30% by mass or less, particularly preferably 3% by mass or more and 25% by mass or less, more particularly preferably 3% by mass or more and 20% by mass or less. Thus, there is a tendency that the impact strength and flexural strength of the molded body manufactured using the molding material are more excellent. In addition, even in the case of a molding thermal history, there is a tendency that dust generation can be better suppressed.

[0078] When the content of the binder in the molding material involved in the present embodiment is set to XB [mass %] and the content of the polyurethane fiber is set to XU [mass %], it is preferred to satisfy the relationship of 0.01≤XU / XB≤0.60, more preferably satisfy the relationship of 0.02≤XU / XB≤0.50, and further preferably satisfy the relationship of 0.03≤XU / XB≤0.45. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0079] When the content of cellulose fiber in the molding material involved in this embodiment is set to XC [mass %] and the content of polyurethane fiber is set to XU [mass %], it is preferred to satisfy the relationship of 0.2≤XU / XC≤5.0, more preferably satisfy the relationship of 0.3≤XU / XC≤3.0, and further preferably satisfy the relationship of 0.4≤XU / XC≤2.5. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0080] 1.2.3 Other resin fibers

[0081] The resin in the molding material according to the present embodiment may also contain resin fibers (other resin fibers) other than polyurethane fibers. By containing other resin fibers, the resin fibers function as fillers close to the wettability of the adhesive, thus being advantageous in further strengthening the molded body.

[0082] Examples of other resin fibers include polyester fibers, acrylic fibers, nylon fibers, and acetate fibers.

[0083] The average length of the other resin fibers is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and further preferably 100 μm or more and less than 400 μm. This tends to make the impact strength and bending strength of the molded body made using the molding material more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0084] The average diameter of the other resin fibers is not particularly limited, but is preferably less than 100 μm, more preferably 3 μm or more and less than 50 μm, and further preferably 5 μm or more and less than 20 μm. This tends to make the impact strength and bending strength of the molded body made using the molding material more excellent. In addition, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0085] The average aspect ratio of the other resin fibers, that is, the average length relative to the average diameter, is not particularly limited, but is preferably 10 or more and 1000 or less, and more preferably 15 or more and 100 or less. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made more excellent. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0086] The content of other resin fibers is preferably 1% by mass or more and 30% by mass or less relative to the total mass of the molding material, more preferably 2% by mass or more and 25% by mass or less, and further preferably 3% by mass or more and 20% by mass or less. Thus, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made more excellent. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0087] When the content of the binder in the molding material involved in this embodiment is set to XB [mass %] and the content of other resin fibers is set to XO [mass %], it is preferred to satisfy the relationship of 0.01 ≤ XO / XB ≤ 0.45, more preferably satisfy the relationship of 0.02 ≤ XO / XB ≤ 0.36, and further preferably satisfy the relationship of 0.03 ≤ XO / XB ≤ 0.30. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0088] When the content of cellulose fibers in the molding material involved in the present embodiment is set to XC [mass %] and the content of other resin fibers is set to XO [mass %], it is preferred to satisfy the relationship of 0.1≤XO / XC≤3.8, more preferably satisfy the relationship of 0.2≤XO / XC≤2.1, and further preferably satisfy the relationship of 0.3≤XO / XC≤1.7. As a result, there is a tendency that the impact strength and bending strength of the molded body manufactured using the molding material can be made better. In addition, even in the case of a molding heat history, there is a tendency that dust generation can be better suppressed.

[0089] 1.2.4 Molecular weight distribution

[0090] The resin contained in the molding material according to the present embodiment has a molecular weight distribution curve obtained by the GPC method using chloroform as an eluent, and has a local maximum 1 when the weight average molecular weight is 50,000 to 150,000, and has a local maximum 2 when the weight average molecular weight is 75,000 to 300,000, and the area value of the local maximum 2 is smaller than the area value of the local maximum 1. In this way, by making the resin have a moderate high molecular weight component, even if the resin is thermally decomposed due to the molding heat history, the generation of dust can be better suppressed.

[0091] The GPC method refers to gel permeation chromatography, which can be measured, for example, by the following steps. A device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) are connected in series on a GPC device (ACQUITY APC, manufactured by Waters) is used as a measuring device. The measurement sample (molding material) is dissolved in chloroform as an eluent, filtered with a filter with a pore size of 0.45 μm, and the dissolved component is subjected to GPC analysis, thereby obtaining a molecular weight distribution curve of the resin. Here, the column temperature is 40°C, and an IR detector is used as a detector. In addition, polystyrene (manufactured by Agilent) is used as a standard sample.

[0092] Note that, by using chloroform as an eluent, a resin soluble in chloroform can be measured. Examples of the resin soluble in chloroform include polybutylene succinate, polylactic acid, and polyurethane.

[0093] As a peak calculation method, for example, it can be as follows. The chromatogram is taken as a linear function, and the position where the slope is 0 during differentiation is taken as the peak top. The chromatogram is taken as a linear function, and the position where the slope is 0 during micro-division is taken as the peak boundary. The value of the peak vertically divided from the peak boundary position is calculated as the area value of each peak. It should be noted that when the peaks are fully separated, the area value can be processed as a separate peak. In addition, when two overlapping peaks can be fully distinguished, they are processed as shoulder peaks, and the root of the small peak is drawn out with a straight line to calculate the area value. In addition, peak separation software can be used to calculate the area of ​​each peak. However, the consistency rate is more than 90%.

[0094] The resin contained in the molding material involved in this embodiment has a maximum value 1 when the weight average molecular weight is 50,000 to 150,000 in the molecular weight distribution curve obtained by the GPC method using chloroform as the eluent, and the weight average molecular weight is more preferably 50,000 to 130,000, and further preferably 60,000 to 120,000. If the maximum value 1 is within the above range, there is a tendency to better suppress the generation of dust even in the case of a molding heat history. In addition, the maximum value 1 preferably has a weight average molecular weight less than the maximum value 2.

[0095] The resin contained in the molding material according to the present embodiment has a maximum value 2 when the weight average molecular weight is 75000 to 300000 in the molecular weight distribution curve obtained by the GPC method using chloroform as the eluent, and the weight average molecular weight is more preferably 80000 to 280000, and further preferably 85000 to 250000. If the maximum value 2 is within the above range, there is a tendency to better suppress the generation of dust even in the case of a molding heat history.

[0096] Here, (weight average molecular weight of maximum value 2) / (weight average molecular weight of maximum value 1) is preferably greater than 1.0 and less than 3.0, more preferably greater than 1.0 and less than 2.5, and further preferably greater than 1.0 and less than 2.1. In this case, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0097] 1.3 Cross-linking agent

[0098] The molding material according to the present embodiment may further contain a crosslinking agent. By containing a crosslinking agent, it is easy to adjust the molecular weight distribution in the resin, and even in the case of a molding heat history, there is a tendency that dust generation can be more effectively suppressed.

[0099] As the crosslinking agent, a crosslinking agent having a reactive group that can crosslink with polyester or polyurethane is preferred. More specifically, the crosslinking agent preferably has a reactive group selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid. A crosslinking agent having such a reactive group can preferably react with polyester or polyurethane, and it is easy to adjust the molecular weight distribution in the resin, and further, even in the case of a molding heat history, it has a tendency to better suppress the generation of dust.

[0100] As the crosslinking agent, commercially available products can be used, for example, METABLE NP-1901 (manufactured by Mitsubishi Chemical Corporation), DENACOLEX-321 (manufactured by Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether), DENACOLEX-211 (manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (manufactured by Asahi Kasei Corporation, isocyanate), CARBODILITE Elastostab H01 (manufactured by Nisshinbo Chemical Co., Ltd.), MG-670P (manufactured by Riken Vitamin Co., Ltd.), etc. can be mentioned.

[0101] The content of the crosslinking agent is preferably 1% by mass or more, more preferably 2% by mass or more, relative to the total mass of the molding material. In addition, the content of the crosslinking agent is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 6% by mass or less, relative to the total mass of the molding material. If the content of the crosslinking agent is within the above range, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0102] In addition, when the total content of the resin is 100 parts by mass, the content of the crosslinking agent is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.5 parts by mass or more and 15 parts by mass or less, particularly preferably 1.0 parts by mass or more and 10 parts by mass or less, and even more preferably 2.0 parts by mass or more and 8.0 parts by mass or less. If the content of the crosslinking agent is within the above range, even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0103] 1.4 Flame retardant

[0104] The molding material involved in this embodiment may contain a flame retardant. The flame retardant can be a known substance. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, and boron compounds, and organic flame retardants such as bromine compounds and phosphorus compounds.

[0105] As the flame retardant, commercially available products may be used, and examples thereof include Rabitle FP-110 (manufactured by Mitsui Chemicals, Inc., a phosphazene-based flame retardant) and Exolit OP1230 (manufactured by Clariant, a phosphate-based flame retardant).

[0106] The content of the flame retardant is preferably 5% by mass or more and 30% by mass or less relative to the total mass of the molding material, more preferably 8% by mass or more and 25% by mass or less, and further preferably 10% by mass or more and 20% by mass or less. If the content of the flame retardant is within the above range, the flame retardancy of the molded product can be improved, and even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0107] In addition, when the total content of cellulose fiber, binder and polyurethane fiber is 100 parts by mass, the content of flame retardant is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less, and further preferably 10 parts by mass or more and 20 parts by mass or less. If the content of flame retardant is within the above range, the flame retardancy of the molded product can be improved, and even in the case of a molding heat history, there is a tendency to better suppress the generation of dust.

[0108] 1.5 Other ingredients

[0109] The molding material according to the present embodiment may contain other components such as a colorant, an insect repellent, a mildew preventer, an antioxidant, an ultraviolet absorber, an aggregation inhibitor, and a mold release agent.

[0110] The content of other components in the molding material according to the present embodiment is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0111] 2. Manufacturing method of molding material

[0112] Next, a method for producing the molding material according to the present embodiment will be described.

[0113] The molding material according to the present embodiment can be produced by mixing the above-mentioned components, for example. In this case, the timing of mixing the components may be the same or different.

[0114] The molding material according to the present embodiment can be produced by kneading the above-mentioned components, for example. Thus, the compatibilization effect of polyurethane can be effectively exerted. The kneading of the components can be carried out using, for example, a single-screw kneading machine or a double-screw kneading machine.

[0115] The strand-shaped molding material obtained by kneading can be granulated using a granulator such as a strand-type granulator or a water-based hot-cut granulator to obtain a pellet-shaped molding material.

[0116] In addition, as a manufacturing method for molding materials, the following method can also be applied. That is, the kneaded product of the above-mentioned components can also be formed into a sheet, and then, for example, it can be cut into a desired shape using a shredder device to make a granular molding material. The method of molding the kneaded product into a sheet is not particularly limited, and for example, the following methods can be cited: first, the kneaded product is accumulated in the air to form a sheet-like accumulation, and the accumulation is compressed with a calendering device to exclude air and increase the density. Then, a heating furnace is used to heat it in a non-contact manner, and then, a hot pressing device is used to perform hot pressing. The shape and size of the particles obtained by cutting are not particularly limited, for example, a roughly rectangular parallelepiped with a length of more than 2 mm and less than 5 mm can be made.

[0117] The cellulose fibers used in the production of the molding material according to the present embodiment may be materials that have been previously defibrated, and in particular, materials that have been defibrated from a cellulose fiber source containing cellulose fibers such as waste paper and old cloth may be used.

[0118] In addition, when the molding material according to the present embodiment contains other resin fibers, the other resin fibers used in the manufacture of the molding material according to the present embodiment may be subjected to a defibration treatment in advance. In particular, a material obtained by defibration of other resin fiber sources containing other fibers such as old cloth may be used.

[0119] The fiber sources mentioned above, ie, cellulose fiber sources, polyurethane fiber sources, and other fiber sources may be roughly shredded before defibration.

[0120] The fiber source can be shredded into pieces using a shredder with shredding blades in an atmosphere such as air, etc. The shape of the pieces is, for example, a roughly cubic shape or a roughly rectangular parallelepiped shape of several mm square.

[0121] The fiber source fragments are defibrated to become disentangled fibers. Here, the defibration means disentangling each fiber from a state where a plurality of fibers are integrated into one.

[0122] Defibration can be appropriately performed under dry conditions. Here, dry means not being performed in a liquid but in a gas such as the atmosphere. It should be noted that, in order to prevent electrification, etc., the fibers may be sprayed with water, etc. Dry defibration can be appropriately performed, for example, by airflow.

[0123] The defibration of the fiber sources may be performed separately for each fiber source or in a state where a plurality of fiber sources are mixed.

[0124] In addition, as a fiber source, multiple fibers can be used, and more specifically, fibers containing two or more of cellulose fibers, polyurethane fibers, and other resin fibers can be used. As a fiber source containing two or more fibers, for example, a blended product can be cited.

[0125] The fiber source may be defibrated in a state where components other than fibers, such as a binder, a flame retardant, and other components, are contained.

[0126] 3. Molding

[0127] Next, a molded body produced using the molding material according to the present embodiment will be described.

[0128] The molded body can be produced using the above-mentioned molding material.

[0129] The shape of the molded body is not particularly limited, and may be any shape such as a sheet, a block, a sphere, or a three-dimensional shape.

[0130] The molded body can be appropriately produced by, for example, molding the aforementioned molding material by various molding methods such as injection molding and press molding while heating the molding material.

[0131] The heating temperature of the molding material during molding is not particularly limited, but is preferably less than 200°C, more preferably 120°C to 190°C, and further preferably 150°C to 180°C.

[0132] After the above-mentioned molding, for example, machining such as grinding and polishing, or post-processing such as painting and plating may be performed.

[0133] 4. Examples

[0134] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples. Figures 1 to 3 In the composition columns of (Tables 1 to 3), the unit of the numerical value is part by mass.

[0135] 4.1 Preparation of molding materials

[0136] according to Figures 1 to 3 The compositions of (Tables 1 to 3) were used to produce the molding materials of the examples and comparative examples. Specifically, the various components were weighed and put into a twin-screw kneading machine KZW15TW-45MG of TECHNOVEL for kneading. The kneading conditions were: the maximum heating temperature was 180°C and the extrusion output was 1 kg / hr. Then, after being processed into a strand shape, a granulator was used to make a granular molding material.

[0137] It should be noted that as cellulose fibers (cotton fibers, rayon fibers), polyurethane fibers, polyester fibers and acrylic fibers, market clothing recycling products were prepared as fiber sources, and the fiber sources were shredded into roughly cubic shapes of several mm square using a shredder with coarse shredding teeth in the atmosphere, and then blown with air flow to defibrate the fibers.

[0138] The average length of the cellulose fibers contained in the molding material was 1.5 mm, the average diameter of the cellulose fibers was 15 μm, the average length of the polyurethane fibers was 1.5 mm, the average diameter of the polyurethane fibers was 50 μm, and the number average molecular weight of the polyurethane constituting the polyurethane fibers was 60,000.

[0139] For the molding material obtained above, the weight average molecular weight was determined by the GPC method. Specifically, a device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) were connected in series on a GPC device (ACQUITY APC, manufactured by Waters) was used as a measuring device. The measurement sample (molding material) was dissolved in chloroform as an eluent, filtered with a filter having a pore size of 0.45 μm, and the dissolved component was subjected to GPC analysis to obtain a molecular weight distribution curve of the resin. Here, the column temperature was 40°C, an IR detector was used as the detector, and polystyrene (manufactured by Agilent) was used as the standard sample. As a peak calculation method, it is carried out as described above.

[0140] The following additional instructions Figures 1 to 3 (Tables 1 to 3).

[0141] <Adhesive>

[0142] Polypropylene (Prime Polymer, H700)

[0143] Polyethylene (made by Prime Polymer, 2208J)

[0144] · Polylactic acid (Unitica, TERRAMAC TE-2000)

[0145] Polybutylene succinate (Mitsubishi Chemical Corporation, Bio-PBS FZ71PB)

[0146] <Cross-linking agent>

[0147] Cross-linking agent 1 (METABLE NP-1901, manufactured by Mitsubishi Chemical Corporation)

[0148] Cross-linking agent 2 (DENACOL EX-321, manufactured by Nagase ChemteX Co., Ltd., trimethylolpropane polyglycidyl ether)

[0149] Cross-linking agent 3 (DENACOL EX-211, manufactured by Nagase ChemteX Co., Ltd., neopentyl glycol diglycidyl ether)

[0150] Cross-linking agent 4 (Duranate E402-B80B, manufactured by Asahi Kasei Corporation, isocyanate)

[0151] Cross-linking agent 5 (CARBODILITE Elastostab H01, manufactured by Nisshinbo Chemical Co., Ltd.)

[0152] Cross-linking agent 6 (MG-670P, manufactured by Riken Vitamin Co., Ltd.)

[0153] <Elastomer materials>

[0154] ARON Chemical Co., Ltd., ES-A60NX

[0155] 4.2 Manufacture of molded body

[0156] For the molding materials of each embodiment and each comparative example, injection molding was performed using an injection molding machine (manufactured by Nissin Plastic Industry Co., Ltd., THX40-5V) to manufacture the molded bodies for the evaluation of Charpy impact strength, the evaluation of bending elastic modulus, and the evaluation of the number of dusts generated described later. The heating temperature of the molding material during injection molding is 180°C. The molded body for the evaluation of Charpy impact strength is a rectangular plate-shaped molded body with a long side of 80mm±2mm, a short side of 4.0mm±0.2mm, and a thickness of 10.0mm±0.2mm. The molded body for the evaluation of bending elastic modulus and the evaluation of the number of dusts generated is a rectangular plate-shaped molded body with a long side of 80mm±2mm, a short side of 10.0mm±0.2mm, and a thickness of 4.0mm±0.2mm.

[0157] Here, in Figures 1 to 3 In the molding history of (Tables 1 to 3), "re-molding once" means that the material that has undergone the above molding process is re-pelletized and the molding process is performed again in the same manner as above, and "primary" means that only the first molding process is performed without re-pelletization. Figures 1 to 3 In the crosslinking agent adding step of (Tables 1 to 3), "re-making" means adding when the material subjected to the above molding process is pelletized again, and "primary" means adding only when the raw materials are kneaded. In this way, molded bodies for evaluation in each example and each comparative example were obtained.

[0158] 4.3 Evaluation test

[0159] 4.3.1 Charpy impact strength

[0160] The Charpy impact strength of the molded products obtained above for evaluation was measured using an impact tester IT manufactured by Toyo Seiki Seisaku-sho Co., Ltd. in accordance with ISO 179 (JIS K7111). In the measurement of the Charpy impact strength, the hammer weight was 4 J (WR 2.14 N / m), the lifting angle was 150°, the notch remaining width was 8.0 mm ± 0.2 mm, and the notch angle was 45°.

[0161] 4.3.2 Flexural modulus

[0162] The flexural modulus of each of the molded products for evaluation of the flexural modulus obtained above was measured using 68TM-30 manufactured by INSTRON Co., Ltd. in accordance with ISO 178 (JIS K7171). In the measurement of the flexural modulus, the distance between the fulcrums was set to 64 mm.

[0163] 4.3.3 Dust generation

[0164] The above-mentioned Charpy impact strength test was repeated 10 times for the molded body for evaluating the amount of dust generated obtained above, and the amount of particles in the area with a radius of 10 cm near the point of the test machine was measured and compared with the value before the test. The total amount of dust generated was evaluated as "○" when it was less than 20% of the initial value, and the total amount of dust generated was evaluated as "×" when it was more than 20% of the initial value. It should be noted that mm-level fragments exceeding the measurement range of the particle counter are not within the scope of the object, assuming that they are used in the environment of printer heads or sensors, etc.

[0165] 4.3.4 Composite evaluation

[0166] For each of the Examples and Comparative Examples, a composite evaluation was performed according to the following criteria based on the measurement results of the Charpy impact strength, the measurement results of the flexural modulus, and the measurement results of the number of generated dusts.

[0167] (Judgment Criteria)

[0168] A: Dust generation is judged as ○, Charpy impact strength is 2.5 kJ / m 2 and the bending modulus is 1.5 GPa or more.

[0169] B: Dust generation is judged as ○, Charpy impact strength is 2.5 kJ / m 2 or above, or the bending modulus is 1.5 GPa or above (except for the range determined in A above)

[0170] C: Dust generation is judged as ○, Charpy impact strength is less than 2.5 kJ / m 2 , and the bending modulus is less than 1.5GPa

[0171] D: Dust generation judgment ×

[0172] E: Unformable

[0173] 4.4 Evaluation results

[0174] Evaluation results such as Figures 1 to 3 (Tables 1 to 3).

[0175] Depend on Figures 1 to 3 From the results shown in (Tables 1 to 3), it can be seen that: a molding material containing cellulose fibers and a resin, the resin contains a binder and polyurethane fibers, and the resin has a maximum value 1 when the weight-average molecular weight is 50,000 to 150,000, and a maximum value 2 when the weight-average molecular weight is 75,000 to 300,000 in the molecular weight distribution curve obtained by the GPC method using chloroform as the eluent, and the area value of the maximum value 2 is smaller than the area value of the maximum value 1. The molding materials involved in the embodiments that meet the above structure can excellently suppress the generation of dust even in the case of a molding heat history.

[0176] In contrast, the molding materials of the comparative examples that do not satisfy the above structure cannot suppress dust generation in the case of a molding heat history. It should be noted that the molding materials of the reference examples do not contain fiber components, so there is no technical problem of dust generation.

[0177] The following contents can be derived from the above-mentioned embodiments.

[0178] One form of molding material is:

[0179] A molding material,

[0180] It is a molding material containing cellulose fibers and resin.

[0181] The resin contains a binder and polyurethane fibers,

[0182] The resin has a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and has a local maximum value 1 when the weight average molecular weight is 50,000 to 150,000, and has a local maximum value 2 when the weight average molecular weight is 75,000 to 300,000.

[0183] The area value of the maximum value 2 is smaller than the area value of the maximum value 1.

[0184] Alternatively, in one embodiment of the above-mentioned molding material,

[0185] The molding material further contains a cross-linking agent.

[0186] Alternatively, in any of the above-mentioned aspects of the molding material,

[0187] The crosslinking agent has a reactive group selected from carbodiimide, amine, epoxy, unprotected isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid.

[0188] Alternatively, in any of the above-mentioned aspects of the molding material,

[0189] The content of the cellulose fibers is 2% by mass or more and 40% by mass or less relative to the total mass of the molding material.

[0190] Alternatively, in any of the above-mentioned aspects of the molding material,

[0191] The average length of the cellulose fibers is less than 3 mm.

[0192] Alternatively, in any of the above-mentioned aspects of the molding material,

[0193] The average diameter of the cellulose fibers is less than 100 μm.

[0194] Alternatively, in any of the above-mentioned aspects of the molding material,

[0195] The content of the binder is 35% by mass or more and 94% by mass or less relative to the total mass of the molding material.

[0196] Alternatively, in any of the above-mentioned aspects of the molding material,

[0197] The content of the polyurethane fiber is 2% by mass or more and 40% by mass or less relative to the total mass of the molding material.

[0198] The present invention is not limited to the above-mentioned embodiments, and various modifications are possible. For example, the present invention includes a structure that is substantially the same as the structure described in the embodiments, such as a structure with the same function, method and result, or a structure with the same purpose and effect. In addition, the present invention includes a structure that replaces a non-essential part of the structure described in the embodiments. In addition, the present invention includes a structure that has the same effect as the structure described in the embodiments, or a structure that can achieve the same purpose. In addition, the present invention includes a structure in which a known technology is added to the structure described in the embodiments.

Claims

1. A molding material, characterized in that: It is a molding material containing cellulose fibers and resin. The resin contains a binder and polyurethane fibers, The resin has a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and has a local maximum value 1 when the weight average molecular weight is 50,000 to 150,000, and has a local maximum value 2 when the weight average molecular weight is 75,000 to 300,000. The area value of the maximum value 2 is smaller than the area value of the maximum value 1.

2. The molding material according to claim 1, wherein The molding material further contains a cross-linking agent.

3. The molding material according to claim 2, wherein The crosslinking agent has a reactive group selected from carbodiimide, amine, epoxy, unprotected isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid.

4. The molding material according to claim 1 or 2, wherein The content of the cellulose fibers is 2% by mass or more and 40% by mass or less relative to the total mass of the molding material.

5. The molding material according to claim 1 or 2, wherein The average length of the cellulose fibers is less than 3 mm.

6. The molding material according to claim 1 or 2, wherein The average diameter of the cellulose fibers is less than 100 μm.

7. The molding material according to claim 1 or 2, wherein The content of the binder is 35% by mass or more and 94% by mass or less relative to the total mass of the molding material.

8. The molding material according to claim 1 or 2, wherein The content of the polyurethane fiber is 2% by mass or more and 40% by mass or less relative to the total mass of the molding material.